Greenland CCI Surface Elevation Change Products from Cryosat-2 and SARAL/ALtiKa - Simonsen, S.; Khvorostovsky, K.; Sandberg Sørensen, L.; Forsberg, R. (2018)
A long, unbroken sequence of satellite altimetry elevation changes is an essential climate variable. Here,we present the surface elevation change (SEC) record provided in the ESA Greenland ice sheet CCI project, as 5-year running means spanning back to 1992. The 5-year running mean is chosen to show the imprint of climate change on the Greenland ice sheet surface elevation change and limits the imprint of weather variability. We mainly focus on the novel results from ESA's Cryosat- 2 and the French-Indian SARAL/ALtiKa satellite, as this latest generation of radar altimeters provides new opportunities for monitoring Greenland ice sheet SEC. The orbit of Cryosat-2 enables the generation of a higher temporal-resolution data product from Ku-band radar altimetry; a 2-year running mean SEC. This 2-year product shows the inter-annual variability in weather and its imprint in surface elevation. The observational period of SARAL/ALtiKa satellite has now matured, and an experimental SEC product from Ka-band altimetry is being provided in the Greenland ice sheet CCI. The Kaband radar altimetry is less subject to surface penetration in firn covered areas, and map changes in snowfall in the interior region of the Greenland ice sheet. The Greenland ice sheet CCI now provides 11 maps of Greenland SEC generated from Cryosat-2 or SARAL/ALtiKa data. All giving insight into the complex nature of the changing Greenland ice sheet. The emerging patterns from comparing both Cryosat-2 5- year vs. 2-year SEC and Ku-band vs. Ka-band SEC may relate to the interplay between the surface mass balance and internal ice sheet dynamics.